Urban growth management in New Zealand : what factors have influenced urban growth management policies in the Waikato and Bay of Plenty regions over the period 1986 to 2009? : a thesis presented in partial fulfilment of the requirements for the degree of Master of Resources and Environmental Planning at Massey University, Manawatu, New Zealand - Pascall, Kate (Massey University, 2013)
Urban growth management is a planning concept that emerged in the 1960s, and is mainly associated with planning in the United States at that time. It is linked with concerns around urban sprawl and more recently sustainability. Urban growth management has been utilised extensively in the United States, in particular in Portland, as well as Australia and New Zealand. However, it is reasonable to say that the focus on sustainability in the last two decades has given more impetus to the notion of urban limits, and the question of density (Williams, 2004). The purpose of urban growth management policy or ‘urban containment’ as it is often termed is largely to curb urban sprawl, retain rural land for productive use, reduce travel time and costs, and in some cases maintain the economic vitality of the urban core. Typically, policies will advocate the development of brownfield sites over greenfield sites on the periphery (Williams, 2004). The smart growth concept is a more recent form of urban growth management, influencing modern planning since its emergence in the 1990s (Gillham, 2002). The research question is thus: ‘What factors have influenced urban growth management policies in the Waikato and Bay of Plenty regions over the period 1986 to 2009?’ It is believed that this work has not yet been undertaken in New Zealand, and therefore this topic was seen as an ideal contribution to the planning subject. Both areas have recently developed urban development strategies, in a sub-regional context. Moreover, both regions have experienced high rates of population growth over recent decades (Hamilton City Council., Waikato District Council., Waipa District Council., & Environment Waikato., 2009; Tauranga City Council., Western Bay of Plenty District Council., & Environment Bay of Plenty., 2007). The research seeks to find out how each region’s approach to planning for urban development has changed over time.
Abstract not supplied by author. Supplied from introduction.
Keywords: Cities and towns; Growth; Social aspects; City planning; Urban growth management; New Zealand